2008
DOI: 10.1002/sia.2697
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and photoluminescence study of porous thin SiC layer grown onto silicon

Abstract: A porous SiC layer was fabricated by anodization of a 1.6 µm-thin SiC layer deposited onto p-type Si(100) substrate by pulsed laser deposition (PLD), using a hot-pressed 6H-SiC(p) as sputtered target. P-type porous SiC layers were realized by anodization in HF/ethylene glycol (ETG) electrolyte (1 : 1 by vol.) at different etching times. The properties of the porous SiC layer formed by this method were investigated by SIMS, SEM, Fourier transform Infra-Red spectroscopy (FT-IR) and photoluminescence (PL). The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…The SiC etching mechanism proposed by Shor and Kurtz 16 has been generally accepted. 13,[17][18][19][20][21][22][23] According to their hypothesis, anodic etching of SiC in aqueous HF occurs in two steps: oxidation of SiC and dissolution of the formed oxide. They suggested that oxidation of SiC occurs via the following reactions: 16 SiC…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SiC etching mechanism proposed by Shor and Kurtz 16 has been generally accepted. 13,[17][18][19][20][21][22][23] According to their hypothesis, anodic etching of SiC in aqueous HF occurs in two steps: oxidation of SiC and dissolution of the formed oxide. They suggested that oxidation of SiC occurs via the following reactions: 16 SiC…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, most studies have fabricated porous SiC using bulk crystalline SiC, while few studies have fabricated porous SiC from thin films. 2,3,[7][8][9][10][11][12][13][14] SiC thin films are easy to make and relatively inexpensive compared with bulk SiC, and we believe that thin films are suitable for most applications. In many applications, the SiC thin film may be amorphous rather than crystalline: for example, researchers have reported using amorphous SiC thin films to fabricate humidity sensors 2 and ammonia sensors.…”
Section: Introductionmentioning
confidence: 99%
“…The anodic etching of SiC substrates is determined by two concurrent reactions. One is the formation of silicon oxides (SiO and SiO 2 ), and the other is the dissolution of the formed silicon oxides as shown in equations (1)-( 4) [13,[23][24][25]:…”
Section: Resultsmentioning
confidence: 99%
“…What is more, HF/H 2 O 2 does have an effect on enhancing uniformity on 6H-SiC [ 10 ]. The electrochemical etching SiC process in other works, without H 2 O 2 , can be listed as the following [ 11 ]:…”
Section: Resultsmentioning
confidence: 99%